1 Solve the following equations. Match the equation with the correct solution. \( \square \) \( -8+x=3 \) \( x+12=6 \) \( 9 x=-81 \) \( \frac{1}{4} x=3 \) \( \frac{x}{-3}=7 \) \( \square \) \( \qquad \) \( \square \) DRNA A DEOD THE ANSWIR \[ z=9 \] \[ x=-21 \] \( x=-6 \) \( x=12 \) \( z=11 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
Let’s decode those equations and match them up with their solutions in a fun and easy way! - For the equation \( -8 + x = 3 \), simply add 8 to both sides to reveal that \( x = 11 \). - Next, the equation \( x + 12 = 6 \) can be solved by subtracting 12 from both sides, yielding \( x = -6 \). - Now, take a look at \( 9x = -81 \). Dividing both sides by 9 gives us \( x = -9 \). - In the equation \( \frac{1}{4} x = 3 \), multiplying both sides by 4 reveals that \( x = 12 \). - Lastly, \( \frac{x}{-3} = 7 \) leads us to multiply both sides by -3 resulting in \( x = -21 \). Here’s the match-up: - \( -8 + x = 3 \) → \( z = 11 \) - \( x + 12 = 6 \) → \( x = -6 \) - \( 9x = -81 \) → \( z = 9 \) (but note \( x \) should be the solution) - \( \frac{1}{4} x = 3 \) → \( x = 12 \) - \( \frac{x}{-3} = 7 \) → \( x = -21 \) Remember, always double-check your solutions to avoid any unexpected surprises!